Genomic analysis of TNF-related genes with prognosis and characterization of the tumor immune microenvironment in lung adenocarcinoma - Huang, Hua; Yu, Haochuan; Li, Xuanguang; Li, Yongwen; Zhu, Guangsheng; Su, Lianchun; Li, Mingbiao; Chen, Chen; Gao, Min; Wu, Di; Zhang, Ruihao; Cao, Peijun; et al. (Frontiers in Immunology, 2022)
Background: The TNF family makes a difference in the modulation of cellular functions that adjust cellular differentiation, survival, apoptosis, and especially immune functions for cells. The TNF family members also play significant roles in cancer genesis and progression. However, potential valve of TNF family members in lung adenocarcinoma (LUAD) remains to be explored. Methods: The expression of TNF-related genes (TNFRGs) in 1,093 LUAD samples was discovered from the TCGA and GEO datasets. The characteristic patterns of TNFRGs in LUAD were systematically probed. Three distinct molecular subtypes were identified, and a correlation was found between different subtypes and clinical characteristics. A TNF score was constructed to predict overall survival (OS) and therapeutic responses in these LUAD patients. Then, the predictive accuracy of the score was verified. A nomogram was applied for optimizing the clinical applicability range of the TNF score. Results: A high TNF score, characterized by immune and stromal scores, manifested terrible odds of OS. Moreover, the TNF score was connected with immune checkpoints and chemotherapeutic drug sensitivity. Collectively, our comprehensive analysis of TNFRGs in LUAD showed that the TNF could be involved in the diverse and complex tumor microenvironment, clinicopathological features, and prognosis. Conclusions: A TNF-related prognostic model was constructed, and a TNF score was developed. These findings were expected to improve our cognition of TNFRGs in LUAD, pave a new path for the assessment of prognosis, and help develop personalized therapeutic strategies for LUAD patients.